N-glycosylation of NANOG regulates stemness and apoptosis in colon cancer cells - Yin Tian; Yu Zeng; Yun Liu; Jun Ye; Xin Zhang (PLoS ONE, 2025)
To investigate the effect of N-glycosylation on NANOG regulation of colon cancer stem cell characteristics. The GEPA database was used to screen and analyze the expression of N-glycosylase in colon cancer tissues. CD133 + stem cells were selected by magnetic bead sorting of colon cancer HCT116 cells and LoVo cells. Plasmid transfection of colon cancer stem cells was performed by Lipofectamine™ 3000. Cell activity was detected by MTT method. Microsphere formation test was used to detect the diameter and number of stem cell spheres. EdU flow cytometry was used to detect cell proliferation. Scratch assay was used to detect cell migration ability. Western Blot was used to detect the expression level of apoptosis-related proteins. Compared with the control group, colon cancer stem cells transfected with mutant expression vectors with N-glycosylation site deletion had reduced cell activity, decreased proliferation and migration ability; reduced tumor stem cell sphere formation ability; and increased intracellular apoptosis level. Conclusively, The seven N-glycans in the carboxyl terminus of human NANOG are involved in the molecular quality control of NANOG protein and the maintenance of the stem cell characteristics of colon cancer stem cells, further affecting the proliferation and migration ability of colon cancer stem cells.